GP250 NEONATAL JAUNDICE SURVEILLANCE- ARE WE WINNING?. (June 2019) - Yasmeen, Tayyaba; McCue, William; McArthur, Veronica; Jackson, Allan
Abstract : Objectives: To determine the incidence of babies presenting with Serum bilirubin (SBR)>400micromol/litre in last five years (2013–2017) To review the factors leading to admission of neonates with SBR>400micromol/litre in last 2 years (2016–2017) Method: A multicentre retrospective review of the yearly data of neonates<28 days treated for very high SBR>400 micromol/litre across GGC between years2013–2017 was collected from the Laboratory database. Detailed retrospective review of all the neonates treated for SBR>400 micromol/litre in three NNU in 2016 & 2017 was done by case notes, midwifery record notes and online patient database Variables including gestational age, age at presentation, gender, family history, type of feeding, serial bilirubin levels (transcutaneous bilrubinometre (TcB), blood) before and at the time of start of treatment were reviewed to determine the causes of presentation with high bilirubin levels in spite of having a Jaundice surveillance system in place. Results: The number of babies needing treatment due to high SBR (>400micromol/l) has significantly declined from year 2013 to 2017 across GGC (p value=0.002). Total 18 patients with SBR >400micromol/l were admitted in 2016 (n=10) and 2017(n=8). Majority of the babies were male (n=10, 55%), commonest gestational age group was between 37–40 w (n=14, 78%), presenting between 5–10d of life (n=13, 72%) and referred by the community midwives (n=17, 94%). TcB was most commonly used to assess SBR before referral to hospital (n= 11, 61%), majority of the babies received treatment for the first time (n=16, 89%) and most of the babies were breast fed (n=8, 44). Predisposing factors for jaundice included breast feeding (n=10), cephalhematoma/bruising (n=3), Hereditary Spherocytosis (n=1) and G6PD deficiency (n=1). Other factors included lack of close monitoring for jaundice in community (n=8), discrepancy of correlation between TcB and SBR values (n=6), inappropriate plotting on bilirubin charts(n=2). Conclusion: Incidence of babies presenting with SBR>400micromol/l has significantly reduced in last five years. This could be secondary to introduction of TcB in community and improvement in jaundice surveillance system. However there is still margin for improvement as new cases are still presenting either due to inappropriate monitoring in community or discrepancy in co-relation of levels between TcB and SBR.